2007
DOI: 10.1007/s00535-007-2060-x
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein is an independent clinical feature of nonalcoholic steatohepatitis (NASH) and also of the severity of fibrosis in NASH

Abstract: This is the first report to demonstrate consistent and profound elevation of hs-CRP in cases of NASH compared with in cases of simple nonprogressive steatosis. Our results suggest that hs-CRP may be a clinical feature that not only distinguishes NASH from simple nonprogressive steatosis but also indicates the severity of hepatic fibrosis in cases of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
180
2
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(209 citation statements)
references
References 46 publications
16
180
2
11
Order By: Relevance
“…CRP originates in the liver and is increased in people with liver steatosis [32], suggesting a link between chronic inflammation and non-alcoholic fattyliver disease. The association of GGT with insulin resistance, fasting blood glucose and triacylglycerols [33][34][35] and type 2 diabetes [22][23][24] is well described.…”
Section: Discussionmentioning
confidence: 99%
“…CRP originates in the liver and is increased in people with liver steatosis [32], suggesting a link between chronic inflammation and non-alcoholic fattyliver disease. The association of GGT with insulin resistance, fasting blood glucose and triacylglycerols [33][34][35] and type 2 diabetes [22][23][24] is well described.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and TNF-α are the major stimuli responsible for increased hepatic production of C-reactive protein (CRP), fibrinogen and other acute-phase proteins [44,52]. It has been shown that fibrinogen and CRP levels, which are known CVD risk factors, are increased in NAFLD patients, particularly in those with NASH [61,62]. The liver is also an important site of production of plasminogen activator inhibitor-1 (PAI-1), another known risk factor for CVD [44].…”
Section: Biological Mechanisms Potentially Responsible For Acceleratementioning
confidence: 99%
“…This criteria was validated in pediatric NAFLD. 118 Yoneda et al 82 have published the first report to demonstrate consistent and profound elevation of high-sensitivity CRP in cases of NASH compared with simple steatosis. The high-sensitivity CRP is superior to anthropometric parameters as a marker of the metabolic consequences of obesity.…”
Section: Biomarkersmentioning
confidence: 99%
“…27,46,[79][80][81] Research results has shown HOMA-IR has notably higher levels in NASH in comparison with simple steatosis, especially in obese children. 32,36,44,[82][83][84][85] In addition, the degree of liver involvement as diagnosed by ultrasonography and level of insulin secretion (oral glucose tolerance test) and IR (HOMA-IR) have shown compatible results. 22,30 There are also some studies based on comparison between different techniques of insulin sensitivity measurement, cutoff point 26,79 and accompanying biochemical test such as a lipid profile.…”
Section: Insulin Resistance Testsmentioning
confidence: 99%
See 1 more Smart Citation